The AI power paradox: Can states learn to govern artificial intelligence before its tool late? - Bremmer, Lan and Suleyman, Mustafa (Foreign Affairs)
Its 2035, and artificial intelligence is everywhere. At systems rune hospitals, operate air leis, and battle each other in the courtroom. Productivity spiked to unprecedented levels, and countless previously unimaginable business have scaled at blistering speed, generating immense advances in well-being New products, cures and innovations hit the market daily, as science and technology kick into overdrive and yet the world is growing both more unpredictable and more fragile, as terrorists find new ways to menace societies with intelligent, evolving cyber weapons and white collar workers lose their jobs en masse. Just a year ago, that scenario would have seemed purely fictional; today, it seems nearly inevitable. Generative at systems can already write more